On the synonymy of two wolf spider species of the genus Alopecosa (Araneae, Lycosidae) from the steppe zone of Russia - Azarkina, Galina N.; Esyunin, Sergei L.; Kuz'min, Evgeniy A.; Marusik, Yuri M. (Zootaxa, 2016)
Alopecosa atypica Ponomarev, 2008 is known from the holotype male collected in Western Kazakhstan. Here we synonymize it with A. cronebergi (Thorell, 1875), which was described from two syntype females from the Volga River and Daghestan. This species is redescribed in detail and its distribution is shown to be restricted to Russia and Ukraine, and previous records from Hungary are probably mistaken.